Comparison of performance Islamic banking & Conventional banking before and after crisis / Nadzirah Mat Jaos - Mat Jaos, Nadzirah (Faculty of Business and Management, 2010)
This paper studies empirically the performance of Islamic banking and conventional banking before and after crisis during period 2004 until 2009. The Islamic bank selected is Bank Islam Malaysia Berhad (BIMB) and conventional banking is Malayan Banking Berhad (Maybank). This study follows the basic theoretical model of financial ratio analysis by Rose (2002).The result indicate that the performance of Islamic and conventional banking include return on asset (ROA), return on equity (ROE) and debt ratio (DR) before and after crisis.